2002
DOI: 10.1164/rccm.2109018
|View full text |Cite
|
Sign up to set email alerts
|

Diisocyanate Antigen-stimulated Monocyte Chemoattractant Protein-1 Synthesis Has Greater Test Efficiency than Specific Antibodies for Identification of Diisocyanate Asthma

Abstract: We previously reported that diisocyanate-human serum albumin (DIISO-HSA) stimulated production of monocyte chemoattractant protein-1 (MCP-1) by peripheral blood mononuclear cells is significantly associated with a clinical diagnosis of diisocyanate asthma (DA). Others have reported that antibodies for DIISO-HSA are specific but insensitive markers of DA. This study was performed to evaluate test characteristics of the in vitro MCP-1 assay compared with DIISO-HSA-specific immunoglobulin (Ig) G and IgE in identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 28 publications
3
60
2
Order By: Relevance
“…further demonstrated that isocyanatealbumin induced in vitro MCP-1 production by PBMCs was associated with clinical responses to inhalation challenge tests. 15 The present data suggest chemokine responses represent part of a much broader cellular reaction triggered by isocyanate, which may contribute to the chemical's potent (hyper)sensitizing capability.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…further demonstrated that isocyanatealbumin induced in vitro MCP-1 production by PBMCs was associated with clinical responses to inhalation challenge tests. 15 The present data suggest chemokine responses represent part of a much broader cellular reaction triggered by isocyanate, which may contribute to the chemical's potent (hyper)sensitizing capability.…”
Section: Discussionmentioning
confidence: 68%
“…4,7 Instead, limited recent studies suggest that human monocyte responses may play an important role in clinical isocyanate exposure outcome. 15,16 Monocytes are crucial cells of the innate arm of the immune system that circulate in an immature form, and differentiate into "tissue macrophages", dendritic cells and alveolar macrophages. [17][18][19][20] Monocytes possess the capacity to modulate immune responses by secreting chemokines and processing/presenting exogenous and "self" antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte chemoattractant protein (MCP)-1 seems to be a specific and sensitive tool in the diagnosis of OA due to isocyanates [42]. What is the validity of MCP-1 assessment in OA due to other agents besides isocyanates?…”
Section: Seventy-fivementioning
confidence: 99%
“…to complex (unconjugate) platinum salts, trimellitic and acid anhydrides [18,19]. In the case of LMW compounds, particularly some of the most common causes of OA, like isocyanates, the sensitivity and specificity of tests assessing the IgE response is variable, being good for some [20] and less satisfactory for others [21,22]. It is also worth noting that results of both skin and in-vitro tests of IgE-mediated sensitivity may fall to a level below detection when workers are removed from exposure [12].…”
Section: Immunological Assessmentmentioning
confidence: 99%
“…An increased CD69 expression on peripheral blood eosinophils after specific inhalation challenge with LMW compounds has been described [25]. Recently, an in-vitro assay measuring production of the C-C chemokine monocyte chemotactic protein (MCP)-1 by peripheral mononuclear cells after 48 h of stimulation with diisocyanate/human serum albumin (HSA) reported 79% sensitivity and 91% specificity in identifying workers with SIC-confirmed OA [22]. At present, however, such techniques are used as research tools and not for clinical practice.…”
Section: Immunological Assessmentmentioning
confidence: 99%